A study of Nutritional and Chemical Content in One Kind Chamomile Tea for Infant and Children (Journal of the College of Education for Women, 2019)
This study has been performed for knowing the nutritional and chemical content of one kind chamomile tea for infant and children available in the pharmacy. The results have been showed that the percentage of essential compounds which represented with moisture, protein, fat, carbohydrate, ash and calories as 7.09%,0.01%,0.01%,92,81%, 0.08% and 371,37 Kal./100g, respectively of dry weight. Also the results have been showed that the percentage of chamomile plant extract that added to the tea as 5.74%. And the result of chemical test for effective materials in alcoholic extract showed consist Tannis, Glycosides, Flavonoids, Alkialoids,and Resins.